2017
DOI: 10.3390/rs9111145
|View full text |Cite
|
Sign up to set email alerts
|

A New Low-Rank Representation Based Hyperspectral Image Denoising Method for Mineral Mapping

Abstract: Abstract:Hyperspectral imaging technology has been used for geological analysis for many years wherein mineral mapping is the dominant application for hyperspectral images (HSIs). The very high spectral resolution of HSIs enables the identification and the diagnosis of different minerals with detection accuracy far beyond that offered by multispectral images. However, HSIs are inevitably corrupted by noise during acquisition and transmission processes. The presence of noise may significantly degrade the qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Therefore, considering that such detectors adopting a sliding window strategy are usually sensitive to the window sizes, different pairs of window sizes are set in order to convincingly reflect their detection performance. Taking account of both characteristics of different hyperspectral images and requirements of different detectors' parameter settings, we define four pairs of window sizes for LRX- (17,7), (17,9), (19,7), and (19,9)-and six pairs of window sizes for SRD- (13,7), (15,9), (17,7), (17,9), (19,7), and (19,9). Besides, we set the optimal value for the regularized parameter of SRD for each hyperspectral image in the experiment.…”
Section: Parameter Settingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, considering that such detectors adopting a sliding window strategy are usually sensitive to the window sizes, different pairs of window sizes are set in order to convincingly reflect their detection performance. Taking account of both characteristics of different hyperspectral images and requirements of different detectors' parameter settings, we define four pairs of window sizes for LRX- (17,7), (17,9), (19,7), and (19,9)-and six pairs of window sizes for SRD- (13,7), (15,9), (17,7), (17,9), (19,7), and (19,9). Besides, we set the optimal value for the regularized parameter of SRD for each hyperspectral image in the experiment.…”
Section: Parameter Settingsmentioning
confidence: 99%
“…These spectra are represented by hundreds of continuous bands that can meticulously describe the characteristics of different materials to recognize their subtle differences [3]. Therefore, owing to this good discriminative property of hyperspectral image, it has been widely used in many remote sensing research fields [4,5], such as image denoising [6,7], hyperspectral unmixing [8,9], band selection [10,11], target detection [12,13], and image classification [14,15]. They all have important practical applications in geological exploration, urban remote sensing and planning management, environment and disaster monitoring, precision agriculture, archaeology, etc.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is also worth mentioning the matrix factorization approaches, examples are References [38][39][40], which are more suited to the fusion of low resolution hyperspectral images with high resolution multispectral ones. In this case, in fact, the spectral variability becomes a serious concern to be handled carefully by means of unmixing oriented methodologies [41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…In [4,5], it was shown that the SI noise in some HSIs is colored, i.e., spectrally non-white. With the improvement of the sensitivity in the electronic components [6], the resolution of the charged coupled device (CCD) camera has improved significantly, so that the photon noise has become as dominant as the signal-independent electronic noise in HSI data collected by new-generation hyperspectral sensors [7][8][9][10]. In this case, the assumption of additive and stationary noise model is not appropriate although this hypothesis is plausible for HSIs where the SI noise is dominant while SD noise, which depends on the useful signal level, is negligible.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the assumption of additive and stationary noise model is not appropriate although this hypothesis is plausible for HSIs where the SI noise is dominant while SD noise, which depends on the useful signal level, is negligible. Therefore, in this paper, we use the widely accepted noise model in [7][8][9][10] including both signal-dependent and signal-independent noise. There are few denoising algorithms based on the photon noise model.…”
Section: Introductionmentioning
confidence: 99%